A Suppressed Demand Analysis Method of the Transportation Disadvantaged in Policy Making - Duvarcı, Yavuz; Duvarcı, Yavuz; Mizokami, Shoshi (Taylor and Francis Ltd., 2009)
This paper proposes a method for estimating transportation supply requirements when the suppressed demand of the transportation disadvantaged (TD) can be calculated and added to existing demand for travel. The underlying assumption is that the travel conditions of these TD groups must be equal to the 'conventional' demand, known as 'full release'. Utilising the modelling approach for TD, suppressed demand analysis, diagnosis of difficulties and equity between conventional and disadvantaged groups were realised, while elaborating special cases for the most vulnerable TD groups (such as elderly and disabled persons) and simultaneously identifying areas of difficulty. From the early virtual results, it is concluded that, for the full release of suppressed trips (only a 5% increase), policy makers must be ready to face some financial burdens, requiring coordination of effort to both standardise these TD groups and reduce the costs incurred by operators.
Keywords: Suppressed travel demand; Transportation disadvantage; Disabled and elderly persons